2010
DOI: 10.1007/s00467-010-1511-4
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of left ventricular mass with antihypertensive therapy in children with hypertension

Abstract: There is paucity of data on the regression of left ventricular hypertrophy (LVH) in hypertensive children. This study assessed the effects of antihypertensive therapy on left ventricular mass in children with and without LVH. Medical records of hypertensive patients who had a baseline and follow-up echocardiogram (echo 1, echo 2) were reviewed. Fifteen of 22 treated patients had LVH at echo 1. Enalapril alone or combined was used in 21/22 cases. Echo 2 was performed at a mean interval of 15 +/- 7 months. The L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 27 publications
0
32
0
1
Order By: Relevance
“…The short axis view may be especially advantageous in this setting, because of the systolic lateral motion of the LV that can occur in children. In fact, the short axis is preferred in many studies involving children, which utilize linear dimension assessment of the LV (7, 8). Additionally, the apical 2-chamber view is less frequently utilized in pediatric laboratories, in part because the small rib spaces in children makes the view more technically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The short axis view may be especially advantageous in this setting, because of the systolic lateral motion of the LV that can occur in children. In fact, the short axis is preferred in many studies involving children, which utilize linear dimension assessment of the LV (7, 8). Additionally, the apical 2-chamber view is less frequently utilized in pediatric laboratories, in part because the small rib spaces in children makes the view more technically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…In these rare studies, it could be demonstrated that antihypertensive therapy could induce regression of LVH. [24][25][26] However, no study focused on the association of achieved control of HT with the prevalence of LVH. In our study, children with treated but uncontrolled HT had three times higher prevalence of LVH than children with controlled HT (Figure 2).…”
Section: Association Of Bp Control With Target Organ Damagementioning
confidence: 98%
“…This means that several classes including diuretics, angiotensin converting enzyme inhibitors, angiotensin receptor blockers, calcium channel blockers and beta adrenergic blockers could be chosen as first-line agents. There are preliminary data demonstrating that pharmacologic treatment can be effective in lowering left ventricular mass as well as blood pressure in children (68). …”
Section: Blood Pressurementioning
confidence: 99%